USING BEHAVIORAL ECONOMICS IN PUBLIC POLICIES TO INCREASE ORGAN DONATION - Morato de Andrade, Otávio (LexCult: revista eletrônica de direito e humanidades; v. 8 n. 2 (2024): Sociedade em Conciliação, 2024)
In recent decades, scientific advancements and investments in the healthcare system have reduced biological rejection in organ transplants and enabled more efficient logistics to support these procedures. However, while there has been an expansion in the infrastructure for transplant services, it is observed that organ donation rates in Brazil have not kept pace with this growth, resulting in a deficit of available organs and longer waiting lists. This article aims to address whether it's possible to increase the number of organ donors through the use of insights from behavioral economics, also known as nudges. To achieve this, a statistical survey of transplants in Brazil based on official records will be conducted, along with a compilation of existing legal frameworks in the country. Subsequently, a literature review of behavioral economics concepts will be presented, alongside an analytical examination of their practical contributions in implementing public policies. The conclusion suggests the feasibility of using opt-out and mandatory choice systems, as these interventions can increase the number of organ donors and contribute to saving lives without affecting the donor's or their family's freedom of choice.